h(x) = sin2xcos2x h'(x) = -4cos2xsin2x <--- doubt this is correct -------------------- f(x) = cotx/sinx (unsure on how to do this....) -thx
Follow Math Help Forum on Facebook and Google+
Originally Posted by maybnxtseasn h(x) = sin2xcos2x h'(x) = -4cos2xsin2x <--- doubt this is correct -------------------- f(x) = cotx/sinx (unsure on how to do this....) -thx For the first one try using If you know the derivatives of cotx and sinx, then use the quotient rule on the second one
Originally Posted by maybnxtseasn h(x) = sin2xcos2x h'(x) = -4cos2xsin2x <--- doubt this is correct -------------------- f(x) = cotx/sinx (unsure on how to do this....) -thx you need to use the product rule ... or use an identity ... note that product rule again ... or ... use the quotient and chain rules ...
View Tag Cloud